2018
DOI: 10.18632/aging.101488
|View full text |Cite
|
Sign up to set email alerts
|

Linc00472 suppresses proliferation and promotes apoptosis through elevating PDCD4 expression by sponging miR-196a in colorectal cancer

Abstract: Long intergenic non-coding RNA Linc00472 has been considered as a tumor suppressor in some cancers. However, the function and mechanism of Linc00472 in colorectal cancer has not been well elucidated. In this study, we found that Linc00472 was down-regulated in colorectal cancer tissues and cells. Elevated Linc00472 expression suppressed proliferation and induced apoptosis in colorectal cancer cells. Moreover, Linc00472 acted as a competing endogenous RNA (ceRNA) of miR-196a to release programmed cell death 4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…NSCLC remains one of the foremost malignancies afflicting the lungs, and it is characterized by rapid growth and aggressive features during its progression, leading to a large number of deaths on an annual basis worldwide 21 . Recent reports have indicated that LINC00472 assumes a tumor-suppressive role in various types of cancers, including gastric cancer, epithelial ovarian cancer, and colorectal cancer 22, 23, 24. However, the role of LINC00472 functioning in NSCLC has remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC remains one of the foremost malignancies afflicting the lungs, and it is characterized by rapid growth and aggressive features during its progression, leading to a large number of deaths on an annual basis worldwide 21 . Recent reports have indicated that LINC00472 assumes a tumor-suppressive role in various types of cancers, including gastric cancer, epithelial ovarian cancer, and colorectal cancer 22, 23, 24. However, the role of LINC00472 functioning in NSCLC has remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, decreased expression of LINC00261 indicated a better prognosis in TSCC. Our study found LINC00261 regulated the expression of ENPP4 and ENPP5, however, these two genes have not been Several existing studies indicate that LINC00472 plays an important role in inhibiting tumor development (Shen et al 2015;Su et al 2018;Ye et al 2018). Our study also showed the similar results that higher expression of LINC00472 was associated with better prognosis.…”
Section: Discussionsupporting
confidence: 77%
“…Several existing studies indicate that LINC00472 plays an important role in inhibiting tumor development (Shen et al, 2015; Su et al, 2018; Ye et al, 2018). Our study also showed the similar results that higher expression of LINC00472 was associated with better prognosis.…”
Section: Discussionmentioning
confidence: 99%